The Effect Of Liquidity, Leverage And Profitability On Company Value: Case Study of a Listed Pharmaceutical Sub-Sector Company On the Indonesia Stock Exchange (2018-2022) - Permata, Adilla Cahya; Muktiadji, Nusa; Khim, Soei; Silaen, Uluan (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This Study aiming to know how influence Liquidity, Leverage, and Profitability On Company Value. In sub sector companies pharmacy. Research use approach quantitative. Data collection techniques sample use purposive sampling with amount sample as many as 7 companies. The type of data used is secondary data from report finance 2018-2022. This Study use statistical analysis and multiple linear analysis with using SPSS 26. The results of partial test research or t test shows that variable Liquidity (current ratio) and profitability (return on assets) have an effect to Company Value (price to book value), whereas Leverage (debt to equity ratio) no influential to Company Value (price to book value). Based on simultaneous testing or the f test shows that variable Liquidity (current ratio), leverage (debt to equity ratio), and profitability (return on assets) have an effect to Company Value (price to book Value). Keywords :​ Liquidity (current ratio), leverage (debt to equity ratio), and profitability (return on assets) have an effect to Company Value (price to book Value).